The Effect of Sales Promotion and Store Atmosphere on Hedonic Shopping Motivation and Impulsive Buying Behavior in Hypermart Manado City - Nova Christian Mamuaya (DeReMa (Development Research of Management): Jurnal Manajemen, 2018)
The purpose of this research is to know and analyze the effect of sales promotion and store atmosphere on hedonic shopping motivation and impulsive buying of Hypermart consumers in Manado City. The method used in this research is explanatory survey method; with 175 consumers who shop at Hypermart in Manado City as sample with convenience sampling technique; primary data with data collecting technique using questionnaire instrument with Likert scale and structural equation modeling analysis technique with Lisrel 8.80 program. The result of this research shows that sales promotion has positive and significant effect on hedonic shopping motivation; store atmosphere has positive and significant effect on hedonic shopping motivation; sales promotion has positive and significant effect on impulsive buying; store atmosphere has positive and significant effect on impulsive buying; and hedonic shopping motivation has positive and significant effect on impulsive buying of Hypermart consumers in Manado City. Impulsive buying will be improved if Hypermart management in Manado City is able to increase hedonic shopping motivation with the most dominant indicator is “shopping for value”, where hedonic shopping motivation will be improved if Hypermart management in Manado City can increase sales promotion with the most dominant indicator is “sample giveaway program” and store atmosphere with the most dominant indicator is “in-store appearance”. Bahasa Indonesia Abstrak: Tujuan penelitian ini adalah ingin mengetahui dan menganalisis pengaruh promosi penjualan dan atmosfir toko terhadap motivasi belanja hedonik dan pembelian impulsif konsumen Hypermart di Kota Manado. Metode yang digunakan dalam penelitian ini adalah explanatory survey; dengan sampel 175 orang konsumen yang berbelanja di Hypermart Kota Manado dengan teknik convenience sampling; data primer dengan teknik pengumpulan data menggunakan instrumen kuesioner dengan skala Likert dan teknik analisis structural equation modeling dengan program Lisrel 8.80. Hasil penelitian menunjukkan promosi penjualan berpengaruh positif dan signifikan terhadap motivasi belanja hedonik; atmosfir toko berpengaruh positif dan signifikan terhadap motivasi belanja hedonik; promosi penjualan berpengaruh positif dan signifikan terhadap pembelian impulsif; atmosfir toko berpengaruh positif dan signifikan terhadap pembelian impulsif; dan motivasi belanja hedonik berpengaruh positif dan signifikan terhadap pembelian impulsif konsumen Hypermat di Kota Manado. Pembelian impulsif akan mampu ditingkatkan jika manajemen Hypermart di Kota Manado mampu meningkatkan motivasi belanja hedonik dengan indikator yang paling dominan adalah “belanja untuk nilai”, di mana motivasi belanja hedonik akan mampu ditingkatkan jika manajemen Hypermart di Kota Manado mampu meningkatkan promosi penjualan dengan indikator yang paling dominan adalah “program pemberian sampel” dan atmosfir toko dengan indikator yang paling dominan adalah “interior toko”.